Optimization of Clove Oil Nanoemulsions: Evaluation of Antioxidant, Antimicrobial, and Anticancer Properties - José Nabor Haro-González; Brenda Nathalie Schlienger de Alba; Moisés Martínez-Velázquez; Gustavo Adolfo Castillo-Herrera; Hugo Espinosa-Andrews (Colloids and Interfaces, 2023)
Clove essential oil is traditionally used as an anesthetic, analgesic, or insecticide, and recently, its applications as an antimicrobial, antioxidant, or anticancer agent have been explored. Nanoemulsions are thermodynamically unstable dispersions (d < 100 nm) produced by mixing two immiscible phases, which, in many cases, improve the stability and biological activities of functional ingredients for pharmaceutical, cosmetic, or food applications. This research optimized the formation of clove essential oil nanoemulsions by employing response surface methodology. The surfactant concentration was minimized by modifying the percentage of clove oil (0–100%), surfactant content (1–4%), and oil phase content (0–20%). In the optimum conditions, a nanoemulsion (93.19 ± 3.92 nm) was produced using 1.0% surfactant and 2.5% oil phase of which 50.7% was clove essential oil. The optimized nanoemulsion was stable in rapid stability tests (centrifugation, freezing–thawing, and heating–cooling), but its average droplet size increased during storage at different temperatures. The nanoemulsion contains a phenolic content equivalent to 736 mg gallic acid/mL. However, the antioxidant capacity of the essential oil (IC50 = 0.78 µg/mL) was dismissed in the nanoemulsion (IC50 = 2.43 µg/mL). The antimicrobial activity of the nanoemulsion showed strain–dependent behavior with MIC ranging from 0.0468 to 0.75 mg/mL, where E. coli and S. typhimurium were the most susceptible pathogenic bacteria. Finally, nanoencapsulation of clove oil showed higher in vitro cytotoxic activity against Caco–2 cancer cells (227 μg/mL) than free clove essential oil (283 μg/mL), but nanoemulsion (306 μg/mL) was less effective than oil (231 μg/mL) in the HT–29 line. This research shows the potential of clove essential oil nanoemulsions for developing biological therapies to treat diseases.